2015
DOI: 10.1111/gcb.13051
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of warming and increased snowfall on Arctic tundra plant phenology over the past two decades

Abstract: Recent changes in climate have led to significant shifts in phenology, with many studies demonstrating advanced phenology in response to warming temperatures. The rate of temperature change is especially high in the Arctic, but this is also where we have relatively little data on phenological changes and the processes driving these changes. In order to understand how Arctic plant species are likely to respond to future changes in climate, we monitored flowering phenology in response to both experimental and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
192
4
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(215 citation statements)
references
References 77 publications
11
192
4
8
Order By: Relevance
“…A long‐term warming experiment also found that phenology of high arctic plants was not responsive to warming, but year‐to‐year variation in phenology could be explained by snowmelt date (Bjorkman, Elmendorf, Beamish, Vellend, & Henry, 2015). Temperatures are warming in arctic ecosystems at unprecedented rates (Serreze & Barry, 2011), but our data suggest that warming within the range of our OTC treatment (2.4°C on sunny days) may not delay the onset of senescence even if conditions are still conducive for continued photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A long‐term warming experiment also found that phenology of high arctic plants was not responsive to warming, but year‐to‐year variation in phenology could be explained by snowmelt date (Bjorkman, Elmendorf, Beamish, Vellend, & Henry, 2015). Temperatures are warming in arctic ecosystems at unprecedented rates (Serreze & Barry, 2011), but our data suggest that warming within the range of our OTC treatment (2.4°C on sunny days) may not delay the onset of senescence even if conditions are still conducive for continued photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Melt of the winter snowpack occurred at approximately the same time in both years, but after this the 2 years diverged substantially. Other work has shown that that timing of snowmelt influences phenological stages (Bjorkman et al., 2015; Rosa et al., 2015; Semenchuk et al., 2016), but on an annual basis, photoperiod and warmer temperatures are the best predictors of bud break (Rosa et al., 2015). In the present study, the snow melted at a similar time, but temperatures stayed lower later in 2016 compared to 2015.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In small Arctic catchments, snowmelt is often the most important hydrological driver and generates the majority of annual discharge [17]. The timing of snowmelt, as opposed to temperature, also drives the onset of vegetation phenology and influences subsequent phenological phases and overall fitness of individual plants [18,19]. On a regional scale, spring snow cover in May and June in the Northern Hemisphere has decreased drastically in the last 30 years following trends of increasing air temperatures and reductions in sea ice extent and duration [20].…”
Section: Introductionmentioning
confidence: 99%